2010
DOI: 10.1111/j.1399-3046.2009.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of acute and chronic renal function in children following matched related donor hematopoietic stem cell transplantation

Abstract: Acute and chronic renal impairment are important complications after HSCT. A prospective study was conducted to investigate the glomerular renal function in children who received allogeneic HSCT from matched related donors. Non-radiation conditioning regimens were used in all but one patient. CrCl and serial measurements of serum creatinine were evaluated prior to HSCT, within the first 100 days and one yr after. AKI was defined as at least a 1.5-fold rise in pre-HSCT serum creatinine within the first 100 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 21 publications
(40 reference statements)
9
46
2
6
Order By: Relevance
“…This is similar to other pediatric studies reporting a prevalence of 10–11% at 1-year 20, 21 . Adult studies report a higher prevalence compared to pediatric studies 39 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is similar to other pediatric studies reporting a prevalence of 10–11% at 1-year 20, 21 . Adult studies report a higher prevalence compared to pediatric studies 39 .…”
Section: Discussionsupporting
confidence: 91%
“…Previously, Kistvan et al 20 had reported the incidence of AKI to be 21% in their prospective study of 66 pediatric HSCT recipients. Recently, Ileri et al 21 published a prospective study of 61 pediatric myeloablative and allogenic HSCT recipients and reported the incidence of AKI to be 42% within the first 100 days posttransplant. A recent systemic review of AKI in pediatric HSCT recipients included five observational studies and concluded that one-third of pediatric HSCT recipients developed AKI 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time from transplant to AKI in different studies ranged from a mean of 28 ± 29 days (range 2–90) to a median of six wk (range 2–13) . Subgroup analysis completed by a single study showed that grade 3 AKI had an earlier onset than grades 1 and 2 (14.3 ± 3.2 days compared to 35.2 ± 22.5 days) .…”
Section: Resultsmentioning
confidence: 94%
“…found an incidence of 26% in their pediatric series, with nine patients developing SOS after HSCT. Ileri et al . examined 47 pediatric patients after HSCT, of which eight developed SOS.…”
Section: Aki and Sosmentioning
confidence: 99%